Análise multitemporal do uso e cobertura da terra na Reserva Extrativista Marinha da Baía do Iguape - Recôncavo Baiano: Multitemporal land use and land cover analysis of the Iguape Bay Marine Extractive Reserve – Bahian Recôncavo - Souza, Ivonice Sena de; Souza, Ana Paula Sena de; Souza, Rosemeri Melo e (Revista de Geociências do Nordeste, 2025)
This study aimed to analyze land use and land cover dynamics at the Iguape Bay Marine Extractive Reserve (RESEX) employing Landsat images from 1986, 1994, 2003, 2017 and 2022. The Iguape Bay RESEX covers the municipalities of Cachoeira, São Félix and Maragogipe, located in the Bahian Recôncavo region. The employed methodological procedures comprised a bibliographic research, geographic database organization in a GIS environment, data tabulation, digital image processing and map production. Land use and land cover mapping was carried out by the vectorization method. Mapping accuracy encompassing global and Kappa index accuracies was above 90%. Mangrove area expansion by 1.8 km 2 , agricultural class reduction and increase in dense Atlantic Rainforest remnants were noted at the Iguape Bay RESEX over the last 36 years (1986 to 2022). In this context, multitemporal land use and land cover analyses become paramount, as they allow for furthering knowledge on targets exposed to the probable impacts of rising mean sea levels, contributing to REEX coastal planning and management and the formulation of public policies aimed at local fishing communities.